Mechanics of chain-link wire nets with loose connections. (15th October 2015) - Escallón, J.P.; Boetticher, v.; Wendeler, C.; Chatzi, E.; Bartelt, P.
Highlights: We developed a closed-form analytical model to describe the behaviour of chain-link nets. We modelled the different contact interactions between barrier components. We developed a Finite Element model taking into account contact conditions realistically. We provided a description of a rockfall kit able to dissipate 2000 kJ. We demonstrated the accuracy of the modelling scheme using a real-size field test. Abstract: Chain-link wire nets are used for slope stabilization, natural hazard protection systems, mine and tunnel safety and many other important applications. In rockfall protection barriers the nets are designed to withstand dynamic, impulsive loadings. As they are composed of ultra-high strength steel wires with loose three-dimensional connections, the high resistance nets are very flexible and serve to efficiently distribute loads throughout the structure. Rockfall barrier design requires accurate numerical simulations. In this work, a Finite Element model of chain-link nets is developed. To treat the complex contact interactions among chain-link elements and rockfall barrier components we develop a computational scheme relying on a general contact algorithm. The non-linear force displacement response of the net obtained in tensile quasi-static laboratory tests is successfully reproduced by the numerical model. The model parameters are obtained by optimization techniques. The calibrated chain-link model with contact is shown to successfully simulate a full-scale test of a flexible rockfall protection barrier. The computational schemes allow us to accurately model the mechanical behaviour of chain-link wire nets with loose connections.